2006
DOI: 10.1055/s-2005-837501
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Age and Recovery Duration on Performance During Multiple Treadmill Sprints

Abstract: The aim of this study was to investigate the effects of age and recovery duration on performance during multiple treadmill sprints. Twelve boys (11.7 +/- 0.5 y) and thirteen men (22.1 +/- 2.9 y) performed ten consecutive 10-s sprints on a non-motorised treadmill separated by 15-s (R15) and 180-s (R180) passive recovery intervals. Mean power output (MPO), mean force output (MFO), running velocity, step length, and step rate were calculated for each sprint. Capillary blood samples were drawn from the fingertip a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
46
1
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 23 publications
5
46
1
5
Order By: Relevance
“…This supports the assumption that the recovery process among children is faster than in adults [7,29], and that even overweight children are able to maintain exercise intensity relatively well throughout repeated sprints, in spite of their excessive weight and low aerobic capacity. In contrast, PD was higher in overweight children, indicating greater fatigue, compared to that of non-obese children, who were able to maintain their peak power with no significant reduction during RST [24,25]. In addition, it should be emphasized that PD is determined relative to the personal results, which were far worse in the obese children of the present study compared to results in studies of non-obese children or adult athletes [9,21,31].…”
Section: Discussioncontrasting
confidence: 63%
See 3 more Smart Citations
“…This supports the assumption that the recovery process among children is faster than in adults [7,29], and that even overweight children are able to maintain exercise intensity relatively well throughout repeated sprints, in spite of their excessive weight and low aerobic capacity. In contrast, PD was higher in overweight children, indicating greater fatigue, compared to that of non-obese children, who were able to maintain their peak power with no significant reduction during RST [24,25]. In addition, it should be emphasized that PD is determined relative to the personal results, which were far worse in the obese children of the present study compared to results in studies of non-obese children or adult athletes [9,21,31].…”
Section: Discussioncontrasting
confidence: 63%
“…and young adult males (20.4±0.8 yrs) needed 5 min recovery intervals. In another study, Ratel et al [25] found that running performance decreased less in boys (11.7±0.5 yrs) compared to men (22.1±2.9 yrs.) during ten repeated 10 sec treadmill sprints separated by 15 sec recovery intervals.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…It has, however, been well-established that children experience a lower degree of fatigue [8] and need a shorter time to recover [9] than adults during high-intensity exercise. These differences could be explained by maturation-related development of force/power generation capacity [10], anaerobic capacity [11,12], and glycolytic enzyme system [13].…”
Section: Introductionmentioning
confidence: 99%